2010
DOI: 10.4028/www.scientific.net/jnanor.11.85
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nano Structured SiOC Thin Film for Low k Application

Abstract: In our study, the dielectric properties of SiOC low k thin film derived from polyphenylcarbosilane were investigated as a potential interlayer dielectrics for Cu interconnect technology. A SiOC low k thin film was fabricated onto a n-type silicon wafer by dip coating using 30wt % polyphenylcarbosilane in cyclohexane. Curing of the film was performed in air at 300°C for 2h. The thickness of the film ranges from 1 μm to 1.7 μm. The dielectric constant was determined from the capacitance data obtained from meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…However, by keeping an orientation upright (u) position, for which the energy barrier for H 2 drift is only 1 meV, hydrogen may drift over the graphene surface rather than stay on one binding site, even at a low temperature. Indeed, we observed that hydrogen molecules were floating around on a graphene surface and on a nanotube, even at 20 K, through our first-principle molecular dynamics simulations [36].…”
Section: Hydrogen Adsorption On Perfect Graphenementioning
confidence: 85%
“…However, by keeping an orientation upright (u) position, for which the energy barrier for H 2 drift is only 1 meV, hydrogen may drift over the graphene surface rather than stay on one binding site, even at a low temperature. Indeed, we observed that hydrogen molecules were floating around on a graphene surface and on a nanotube, even at 20 K, through our first-principle molecular dynamics simulations [36].…”
Section: Hydrogen Adsorption On Perfect Graphenementioning
confidence: 85%
“…Furthermore, the dielectric constant of the fired PPCS film is attributed to chemical structure, such as Si-C, C-C, C5C and C-H bonds. 10 From these results, it is observed that firing leads to increased recombination between the Si-O due to the breakdown of Si-C bonds in PPCS films. The silicon dioxide film derived from PPCS formed a good surface roughness on the silicon wafer without porosity.…”
Section: Resultsmentioning
confidence: 88%
“…Polyphenylcarbosilane, in which Si–C bonds build the backbone of the polymer, is expected to have a low dielectric constant, since the polarisability of Si–O bond is higher than that of Si–C bond. Furthermore, the dielectric constant of the fired PPCS film is attributed to chemical structure, such as Si–C, C–C, C = C and C–H bonds 10…”
Section: Resultsmentioning
confidence: 99%
“…1a) is one of the carbosilane polymers containing phenyl groups. It has been studied as a SiOC precursor that is applied in dust prevention films on graphite [21,22], low dielectric films [23,24], anti-corrosion film on metals [25,26] and gas separation films [27,28]. PPCS can also be used as a carbon rich ceramic precursor because of the phenyl group in its structure.…”
Section: Introductionmentioning
confidence: 99%